PENCAPAIAN HASIL BELAJAR MATA PELAJARAN ILMU PENGATAHUAN SOSIAL MELALUI MINAT BELAJAR SISWA - Maryam Muhammad (UIN AR-RANIRY, 2015)
Learning is a process of a person in gaining skills, learning skills and attitudes so that it does not come just like that, but it must be carried out deliberately in a certain time anyway. While the study results are around the skills and the results achieved through the learning process in universities and designated with the numbers measured by tests of learning outcomes. In regard to interest a person against an object reflected in the behavior. In the case of interest is motivated by a person's attention to a particular object of interest, such as attention, curiosity is high, and the need for decisive for the selection of the object of his favorite things. Interest that is an element in achieving success for someone. If someone is interested in social studies, all the attention, curiosity, and the need to subject Soasial Sciences, will be higher, so the higher the learning outcomes of subjects who achieved Sciences, Soasial entered. Turns impacted student interest in learning and have a positive influence on the achievement of learning outcomes Sciences, Soasial subjects. The higher the interest of students in learning subjects of Sciences, Soasial, the higher the learning outcomes of subjects Sciences, Soasial achieved. Conversely the lower the student's interest in learning subjects of Sciences, Soasial, then the lower the learning outcomes of subjects who achieved Sciences, Social.